THE FORMATION AND DEVELOPMENT OF THE JUDICIAL SYSTEM IN THE TURKESTAN REGION: A HISTORICAL AND LEGAL ANALYSIS (Eureka Journal of Education & Learning Technologies, 2026)
This article provides a historical and legal analysis of the formation and development of the judicial system in the Turkestan Region. It examines the judicial policy of the Russian Empire, the 1886 Statute on the Administration of Turkestan, qadi and biy courts, imperial judicial institutions, and mechanisms of administrative control. Based on national and foreign scholarship, the article analyzes legal dualism, the preservation of local legal traditions, and their transformation under colonial governance.
Keywords: Turkestan Region, judicial system, qadi courts, biy courts, people's court, Russian Empire, legal dualism, sharia, adat, colonial administration.